2019
DOI: 10.1007/s00217-019-03313-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of Cornelian cherry (Cornus mas L.): a comprehensive review

Abstract: Cornus mas, also known as the Cornelian cherry, is a plant that grows in Eastern Europe and the Middle East. Its green leaves and reddish oval fruits are associated with many beneficial properties such as antioxidative and anti-inflammatory effects. These features are driven by the rich polyphenolic composition, with anthocyanins and iridoids in Cornelian cherry fruits as well as flavonoids and phenolic acids in leaves. The antioxidant behavior as well as the composition significantly depends on the cultivar o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 102 publications
2
74
1
1
Order By: Relevance
“…Knowledge of the medicinal use of C. mas dates back to traditional medicine practices, for example, in Greece, Turkey, Slovakia, and China, where it served for prevention and treatment of gastrointestinal and circulatory disorders, diabetes, diarrhea, and flu. According to the literature reports, fruits were used most frequently, whereas leaves, flowers, and fruit stones were applied to a minor extent [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of the medicinal use of C. mas dates back to traditional medicine practices, for example, in Greece, Turkey, Slovakia, and China, where it served for prevention and treatment of gastrointestinal and circulatory disorders, diabetes, diarrhea, and flu. According to the literature reports, fruits were used most frequently, whereas leaves, flowers, and fruit stones were applied to a minor extent [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fact probably justifies the traditional applications of cornelian cherry [ 2 , 8 ]. Recently, several in vitro and in vivo studies have confirmed antioxidant, anti-inflammatory, antidiabetic, hypolipidemic, anti-atherosclerotic, antimicrobial, and anticancer activity of the fruits [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have pointed to the beneficial effects of polyphenolic substances contained in Cornelian cherry (Cornus mas L., CC). Cornelian cherry is a member of the Cornaceae family and known as a medicinal plant that grows in eastern and southern Europe, southwest Asia and Middle East [8][9][10]. All cultivars of the cornelian cherry have a high biological value, mainly associated with their antioxidant and anti-inflammatory activities which are attributed to a rich polyphenolic composition [11].…”
Section: Introductionmentioning
confidence: 99%
“…Note that cornelian cherry can be mostly found as a shrub growing up to 9 m high as well as, although rarely, as a small tree (Czerwińska & Melzig, 2018). Cornelian cherry (Cornus mas L.) is recognized as a source of polyphenols, tannins, anthocyanins, and iridoids, all of which are present in both its fruits and leaves (Szczepaniak, Kobus-Cisowska, Kusek, & Przeor, 2019;Kucharska, Szumny, Sokól-Letowska, Piórecki, & Klymenko, 2015). Cornelian cherry is a plant grown in the Eastern and Southern regions of Europe and the Middle East, where it has been used in domestic cuisines for centuries (Czyżowska et al, 2017;Rop, Mlcek, Kramarova, & Jurikova, 2010).…”
Section: Introductionmentioning
confidence: 99%